The Motives of the Crusades from The Perspective of Morad Hoffman - Asseri, Ahmed Ibrahim; Abdul Hamid, Faisal @ Ahamad Faisal (Journal Al-Muqaddimah, 2017)
The crusades that the Muslim world faced were motivated by multiple motives. According to Murad Hoffmann’s perspective, she is motivated by defenders. The first: a religious motive, and the second: the motive of revenge against Islamic conquests. This article adopts a descriptive analytical approach in reviewing the Western motives of the Crusades against the Muslim world. We can conclude that religion is an important starting point in the Crusades, and that the Islamic conquests continue to be an influence for Westerners and therefore they do not spare any effort to try to take revenge on the Islamic world because of them.